Serotonin 5-HT1DB Gene's Interaction with Key Brain Regions in Obsessive-Compulsive Disorder - Atmaca, Murad; Onalan, Ebru; Yildirim, Hanefi; Yuce, Huseyin; Koc, Mustafa; Korkmaz, Sevda; Mermi, Osman (Kure Iletisim Grubu A S, 2010)
Objective: The interaction between neuroanatomical and genetic variables in obsessive-compulsive disorder (OCD) was not studied well. The aim of this study was to examine whether the 5-HT1(DB) gene polymorphism has an impact on brain morphology in normal subjects and patients with OCD. Method: Forty-four patients and 44 healthy controls were studied. Brain volume measurements of subjects structural MRI were performed on certain regions of interests such as orbito-frontal cortex (OFC) and thalamus. Genotyping for the 5-HT1B receptor gene G861C polymorphism was performed using venous blood samples. Results: We found significant genotype-diagnosis interaction effects on brain morphology. The stronger effect of 5-HT1(DB) polymorphism on brain morphology in OCD patients than those in controls were determined in the OFC (P<0.05). However, the analysis showed a genotype-diagnosis interaction effect on the volume of the thalamus at a lower threshold. OCD patients with the G allele showed a significant reduction of volumes in the OFC compared to those carrying the C allele (P<0.05). Contrary to the patient group, in the control group, we found no significant morphological differences between subjects with the G allele and those with C allele. Discussion: We suggest that a variation of the 5-HT1(DB) might be affecting brain morphology in OCD patients.
Keywords: 5-HT1(DB); G allele; MRI; OCD; OFC; thalamus